The use of adamantane-containing compounds in polymer chemistry. - Yoba Ngoma, Richard Habib Patrick (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2005.